Impact of an Irrigation Dam on the Transmission and Diversity of Plasmodium falciparum in a Seasonal Malaria Transmission Area of Northern Ghana. (19th March 2020) - Kyei-Baafour, Eric; Tornyigah, Bernard; Buade, Benjamin; Bimi, Langbong; Oduro, Abraham R.; Koram, Kwadwo A.; Gyan, Ben A.; Kusi, Kwadwo A.
Abstract : Water bodies such as dams are known to alter the local transmission patterns of a number of infectious diseases, especially those transmitted by insects and other arthropod vectors. The impact of an irrigation dam on submicroscopic asexual parasite carriage in individuals living in a seasonal malaria transmission area of northern Ghana was investigated. A total of 288 archived DNA samples from two cross-sectional surveys in two communities in the Bongo District of Northern Ghana were analysed. Parasite density was determined by light microscopy and PCR, and parasite diversity was assessed by genotyping of the polymorphic Plasmodium falciparum msp2 block-3 region. Submicroscopic parasitaemia was estimated as the proportional difference between positive samples identified by PCR and microscopy. Dry season submicroscopic parasite prevalence was significantly higher (71.0%, p = 0.013 ) at the dam site compared with the nondam site (49.2%). Similarly, wet season submicroscopic parasite prevalence was significantly higher at the dam site (54.5%, p = 0.008 ) compared with the nondam site (33.0%). There was no difference in parasite density between sites in the dry season (p = 0.90 ) and in the wet season (p = 0.85 ). Multiplicity of infection (MOI) based on PCR data was significantly higher at the dam site compared with the nondam site during the dry season (p < 0.0001 ) but similar between sites during the wet season. MOI at the nondam site was significantly higher in the wet season than in the dry season (2.49, 1.26, p < 0.0001 ) but similar between seasons at the dam site. Multivariate analysis showed higher odds of carrying submicroscopic parasites at the dam site in both dry season (OR = 7.46, 95% CI = 3.07–18.15) and in wet season (OR = 1.73, 95% CI = 1.04–2.86). The study findings suggest that large water bodies impact year-round carriage of submicroscopic parasites and sustain Plasmodium transmission.